Pelatihan Penerapan Pengelolaan Limbah Kulit Buah dan Sayuran pada Usaha Honey Juice Taman Jati Sari Bekasi - Saputra, Yayan; Tambunan, Aron Micael (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Honey juice business is a business in the field of making fruit juices that requires fresh fruit as the main ingredient in making fruit juice, this honey juice business is located in the beautiful garden of Jati Sari Bekasi. In this Honey juice business, there are 4 activities, namely purchasing fresh fruit from fruit farmers, washing fruit, peeling fruit skin, and mashing fruit by means of a blender. However, this honey juice business is not clean, especially in the disposal of fruit skins, therefore it is necessary to hold training on the application of handling fruit and vegetable peel waste so that fruit peel waste in this Honey juice business can be reused by fermentation or what we call eco-enzyme.